2012
DOI: 10.1016/j.ajhg.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in PNPT1 , which Encodes a Polyribonucleotide Nucleotidyltransferase, Impairs RNA Import into Mitochondria and Causes Respiratory-Chain Deficiency

Abstract: Multiple-respiratory-chain deficiency represents an important cause of mitochondrial disorders. Hitherto, however, mutations in genes involved in mtDNA maintenance and translation machinery only account for a fraction of cases. Exome sequencing in two siblings, born to consanguineous parents, with severe encephalomyopathy, choreoathetotic movements, and combined respiratory-chain defects allowed us to identify a homozygous PNPT1 missense mutation (c.1160A>G) that encodes the mitochondrial polynucleotide phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 22 publications
5
78
0
Order By: Relevance
“…2F) that was paternally inherited. Although eye manifestations have not been described in patients with PNPT1 gene mutations, the remaining phenotypic features were consistent with the clinical presentations seen in other patients 18,19 and as both sequence variants were predicted to be deleterious, we consider them to be disease-causing.…”
Section: Resultssupporting
confidence: 76%
“…2F) that was paternally inherited. Although eye manifestations have not been described in patients with PNPT1 gene mutations, the remaining phenotypic features were consistent with the clinical presentations seen in other patients 18,19 and as both sequence variants were predicted to be deleterious, we consider them to be disease-causing.…”
Section: Resultssupporting
confidence: 76%
“…The exact mechanism of how hPNPase old-35 regulates these genes remains to be elucidated and the possibilities may be numerous ranging from RNA degradation, miRNA regulation or RNA import. Moreover, recently mutations in hPNPase old-35 have also been identified that impair respiratory-chain activity [44]. The ETC genes identified in this study identify the specific genes affected by hPNPase old-35 that maybe causative for mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 78%
“…Variants were annotated and filtered using in-house software PolyWeb as described elsewhere. 31 RNA and DNA Analyses DNA was extracted from primary skin fibroblasts as described previously. 22 For cDNA studies of subject 1, cultured fibroblasts were grown with and without cycloheximide treatment, as described previously.…”
Section: Whole-exome Sequencingmentioning
confidence: 99%